A Maqāṣidī Exegesis of Tabdhīr and Isrāf: A Qur'anic Critique of Consumerism in the Culture Runner Phenomenon - Ahmad Majdi Thoriq Abuwidad; Zamzam Qodri; Fejrian Yazdajird Iwanebel (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2025)
Running has transformed from a simple exercise into an urban lifestyle phenomenon that combines fitness, social identity, and consumerism. This transformation raises critical questions about the ethical boundaries of consumption in contemporary Muslim communities, particularly regarding the Qur'anic concepts of tabdhīr (wastefulness) and isrāf (excess). This study examines the runner culture through the lens of Abdul Mustaqim's tafsīr maqāṣidī, a Qur'anic exegetical approach that emphasizes the higher objectives (maqāṣid) of Islamic law, including the preservation of wealth (ḥifẓ al-māl), well-being (ḥifẓ al-nafs), and social justice ('adl). Using qualitative library research with content analysis, this study investigates Qur'anic verses related to tabdhīr and isrāf (Q.S. al-Isrā' [17]:26-27, al-A'rāf [7]:31, al-An'ām [6]:141) and their application to contemporary consumer behavior. The findings reveal that runner culture often manifests characteristics of isrāf through quantitative excess and tabdhīr through purposeless spending driven by social media visibility and brand competition. The study proposes the operationalization of four maqāṣidī values: wasaṭiyyah (balance), maṣlaḥah (social benefit), 'adl (justice), and tawāḍu' (humility) as ethical frameworks for transforming runner culture from consumerist trends into spiritually meaningful practices. This research contributes to contemporary Islamic ethics by demonstrating the relevance of maqāṣidī exegesis in addressing modern lifestyle challenges and offers practical guidance for Muslim communities seeking to balance physical well-being with ethical consumption.